A critical assessment of antimicrobial treatment in uncomplicated Salmonella enteritis - van Duijkeren, E; Houwers, D.J (Veterinary microbiology, 2000)
The human and veterinary literature on the effect of antimicrobials on the clinical and bacteriological cure in uncomplicated Salmonella gastroenteritis is reviewed. Comparison of data on the efficacy of conventional antimicrobials (chloramphenicol, neomycin, ampicillin, amoxycillin, tetracycline, trimethoprim/sulfonamide combinations) and the newer fluoroquinolones indicate that quinolones may shorten the course of clinical disease in contrast to the conventional antimicrobials. Postconvalescent excretion of Salmonella was not affected by the conventional antimicrobials whereas the data on the fluoroquinolones in this respect are conflicting. The fluoroquinolones are the drugs of choice in human medicine for severe Salmonella infections and for the elimination of the carrier state. These drugs have not been evaluated in this respect in veterinary medicine. Well designed prospective placebo-controlled studies regarding the effect of antimicrobials, especially the fluoroquinolones, on the clinical cure and the postconvalescent shedding of Salmonella in animals are imperative to develop optimal therapeutic strategies.